Effect of Sargassum Sp effervescent on surface roughness of acrylic resin - Fitri Endang; Mohammad Dharma Utama; Eri Hendra Jubhari; Edy Machmud; Bashierah Ikasari Syamsul; Irfan Dammar; Vinsensia Launardo (Indonesian Journal of Prosthodontic, 2023)
One type of denture cleaning is effervescent tablet. Brown algae effervescent granules (Sargassum sp) have been demonstrated as denture cleansers but it has not been proven whether these materials affect the surface roughness of acrylic resins. This research analyzes the effect of effervescent Sargassum sp and alkaline peroxide as a soak-ing agent on the surface roughness of acrylic resin plates. This laboratory experimental study with 27 samples of acrylic resin plates divided into three groups; A was immersed in effervescent granules, B was immersed in alka-line peroxide, and C was immersed in aquadest. Immersion was carried out for 15 minutes per day and lasted for 4 consecutive days; everyday each solution was replaced with a new one. Measurement of surface roughness and hardness of samples using Confocal Laser Scan Microscopy. Wilcoxon's test on the alkaline peroxide group showed a p-value of 0.008 (p<0.05) indicating a significant difference in surface roughness values ​​before and after immer-sion. Paired t-test in the algae and aquadest groups showed p>0.05 which means that there is no significant diffe-rence in surface roughness values ​​before and after immersion. It was concluded that Sargassum sp effervescent granule solution does not affect the surface roughness of the acrylic plate.